THE RIGHT TO A FAIR TRIAL - FLORICA BRASOVEANU (Challenges of the Knowledge Society)
Among the general rights of the citizen on finds the free access to justice, the rights to defense and the right to legal security. The jurisprudence based on principles of law and on international treaties, caused the appearance, along the constitutional protection provided by default by a lawyer, of the need of fair and equitable procedures to ensure a balance in the rights of the parties. Today the right to a fair trial is a fundamental right most frequently invoked in front of Romanian courts, as in complaints to the European Court of Human Rights. This study is intended as a guide of the most important solutions that have been promoted to ensure the protection of the right to a fair trial with all the guarantees that are involved, starting with the right of access to justice and ending with the right to adversarial proceedings.